Design of network security system base on vaccination - YaPing Jiang; JunLin Chang (2010 Sixth International Conference on Natural Computation, 2010)
Inspired information processing in biology immune system is a highly parallel and distributed intelligent computation which has learning, memory, and associative retrieval capabilities. In this paper, we design a network security system using an analogy of natural world immunology. We apply not only the immune mechanism that recognizes self or non-self but also cooperation among immune cells of the system. This system defines an immune cell as one agent based on our multi-agent language, which is an extension of concurrent logic programming languages. These agents can detect and reject intrusion by cooperating with each other.